2013
DOI: 10.1111/apt.12440
|View full text |Cite
|
Sign up to set email alerts
|

Smoking does influence disease behaviour and impacts the need for therapy in Crohn′s disease in the biologic era

Abstract: SUMMARY Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 45 publications
(128 reference statements)
3
48
0
5
Order By: Relevance
“…teristics, disease complications, therapeutic interventions, and smoking status demonstrated that in the time-dependent multivariate analysis, smokers were found to have a signifi cantly decreased survival free of stricturing disease (HR 1.5, 1.18-1.90) or perianal complications (HR 1.50; 95% CI, 1.01-1.46), and had a higher risk for requiring thiopurine therapy (HR 1.20; 95% CI, 1.05-1.30) ( 172 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…teristics, disease complications, therapeutic interventions, and smoking status demonstrated that in the time-dependent multivariate analysis, smokers were found to have a signifi cantly decreased survival free of stricturing disease (HR 1.5, 1.18-1.90) or perianal complications (HR 1.50; 95% CI, 1.01-1.46), and had a higher risk for requiring thiopurine therapy (HR 1.20; 95% CI, 1.05-1.30) ( 172 ).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Previous studies have shown that smoking is both a risk factor for relapse of CD in general and for surgical recurrence in particular [14][15][16][17] . A recent multicenter prospective cohort study showed that despite the widespread use of immunosuppressants and anti-TNF antibodies, smokers with CD have a more severe disease course, including greater requirements for treatment, than non-smokers 18) . Furthermore, a retrospective study conducted to evaluate the effects of smoking at diagnosis on the clinical outcomes after endoscopic dilation found that smoking doubles the risk of recurrent stricture formation requiring further intestinal resection or strictureplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Недавно опубликованные результаты когорт-ного исследования, куда вошли 3224 пациента с БК, свидетельствуют о том, что у курильщиков реже наблюдается БК толстой кишки, чем у неку-рящих (7,9% против 10,9; p<0,05), но более вероят-на перианальная БК (29,5% против 26,2; p<0,05) [30]. Данные этого исследования также показали, что у курильщиков чаще, чем у некурящих боль-ных БК, встречается стриктурирующая форма бо-лезни (22,5 и 19,3% соответственно, p<0,05).…”
Section: курение и прогноз болезни кронаunclassified
“…В некоторых исследованиях, в ходе которых изучали зависимость локализации БК от курения, была показана положительная корреляция куре-ния с локализацией болезни в подвздошной киш-ке [33,34], в других была продемонстрирована от-рицательная корреляция курения и БК толстой кишки [30,34,35], а ряд исследований вообще не показал никакой связи между курением и локали-зацией заболевания [36,37,38]. Авторы системати-ческого обзора по данной теме предположили, что одним из возможных объяснений этому явля-ется отсутствие единообразия в определении ста-туса курения [39].…”
Section: курение и прогноз болезни кронаunclassified